Acronymophilia: an update. Issue 6 (1st December 2000) - Isaacs, David; Fitzgerald, Dominic
Abstract : The history, epidemiology, clinical features, and treatment of the epidemic infection, acronymophilia, a sinister scourge of modern medicine are described.